Seventh Pandemic Vibrio cholerae O1 Sublineages, Central African Republic - (:unkn) unknown (My University, 2021)
Four cholera outbreaks were reported in the Central African Republic during 1997–2016. We show that the outbreak isolates were Vibrio cholerae O1 serotype Inaba from 3 seventh pandemic El Tor sublineages originating from West Africa (sublineages T7 and T9) or the African Great Lakes Region (T10).
Keywords: African Research